PENGARUH KINERJA PENGURUS TERHADAP KEPUASAN ANGGOTA KOPERASI MAHASISWA UNIVERSITAS RIAU - Azizah Yendra Shabihah; Makhdalena; Hendripides (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The University of Riau Student Cooperative (KOPMA UR) serves as a platform for economic activities and a vehicle for entrepreneurial education for students. The success of the cooperative is greatly influenced by the performance of the board in managing the organization and providing services to members. Good board performance is expected to increase member satisfaction, which ultimately encourages participation, loyalty, and the sustainability of the cooperative. The purpose of this study is to analyze the influence of board performance on the satisfaction of members of the University of Riau Student Cooperative. The study employs a quantitative approach using descriptive and causal-associative (bivariate) research methods. The study population consists of 50 active members, with total sampling used. Data were collected via a questionnaire using a Likert scale and analyzed using simple linear regression after undergoing validity, reliability, and classical assumption tests. The results indicate that management performance has a positive and significant effect on member satisfaction, with a regression coefficient of 0.802 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) value of 0.552 indicates that 55.2% of the variation in member satisfaction is explained by the performance of the management, while 44.8% is influenced by other factors. These findings suggest that improving the performance of the management—particularly in terms of transparency, service quality, communication, and innovation—plays a crucial role in enhancing member satisfaction and the sustainability of the cooperative.